Efficacy and prognosis of selected therapies for cancers of the central nervous system – meningiomas, astrocytomas and ependymomas - Drewko, Klaudia; Kopeć, Sylwia; Orłowski, Mateusz; Kuźniar, Julia; Kozubek, Patrycja (Journal of Education, Health and Sport, 2025)
Introduction and purpose: There has been a global increase in the prevalence of adults diagnosed with primary brain tumors. Meningiomas are the most common primary brain tumors, the majority are benign. For asymptomatic, slow-growing tumors, observation with imaging studies may be considered. Surgical resection is the main form of treatment. Other options are radiotherapy and chemotherapy. Astrocytomas are biologically and morphologically diverse group of brain tumors divided into two classes. IDH-wild-type tumors are classified as grade IV astrocytomas. They are widespread malignant brain tumors in adults. Despite aggressive therapy consisting of surgical resection, radiotherapy and temozolomide as many as 90% of grade IV gliomas will have a local recurrence. Ependymoma is a primary tumor. The most proper method of treatment is GTR, in addition radiotherapy is considered helpful. Material and Methods: Bibliographic research was limited to papers published between 2014 and 2024. We have analyzed articles with free and paid access. The articles were identified using the PubMed and Google Scholar search, using key terms. Results: The paper focuses on efficacy and prognosis of selected therapies for cancers of the central nervous system with varying degrees of malignancy. This study reviews the prevalence, current diagnostic tools and evidence-based methods. Conclusions: Brain tumor treatment depends on the type of tumor and the patient's condition. Meningiomas can be treated from observation to surgical removal, and if the tumor cannot be completely removed, radiotherapy is used. Low-grade gliomas are treated surgically, while high-grade gliomas require additional chemotherapy and radiotherapy. Modern surgical techniques and stereotactic radiosurgery (SRS) improve treatment results. Ependymoma, a rare CNS tumor, requires complete removal in the case of benign changes, and radiotherapy in the case of higher-grade tumors.